Cognitive mechanisms underlying the associations between inattention and reading abilities. Issue 1 (2nd January 2018) - Plourde, Vickie; Boivin, Michel; Brendgen, Mara; Vitaro, Frank; Robaey, Philippe; Tremblay, Richard E; Dionne, Ginette
ABSTRACT: This study aims to test cognitive skills underlying the association between inattention and reading in early primary school. Teachers rated inattention symptoms when children ( N  = 523–962) were 6–7 years old. Children were assessed at age 7–8 on phonological awareness, rapid automatized naming (RAN), rapid auditory and bimodal processing, vocabulary, and reading (decoding and comprehension). Phonological awareness, RAN of numbers, and vocabulary mediated the association between inattention and both decoding and comprehension. Rapid bimodal processing mediated the association between inattention and decoding, while RAN of colors mediated the association between inattention and comprehension. This study highlights mediators underlying inattention-reading associations.